2020
DOI: 10.1155/2020/7183629
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA CASC2 Enhances 131I Sensitivity in Papillary Thyroid Cancer by Sponging miR-155

Abstract: Long noncoding RNA cancer susceptibility candidate 2 (CASC2) has been reported to play an anticancer role in papillary thyroid cancer (PTC). Radioiodine (131I) is a common option for the treatment of PTC. However, the role and mechanism of CASC2 in 131I sensitivity remain unclear. In this study, 131I-resistant cells were constructed through continuous treatment of 131I. The expression levels of CASC2 and miR-155 were measured by qRT-PCR. The IC50 of 131I was analyzed by cell viability using MTT assay. Flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The primers for quantification of C10orf55, C3orf35, C5orf38, CASC2, MEG3, MYCNOS, SFTA1P, SNHG3, and TMEM105 were described previously [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ] and are presented in Table 1 . The compatibility of all primers and their complementarity to the target sequence was checked using the Basic Local Alignment Search Tool (BLAST), National Center for Biotechnology Information (NCBI), Bethesda, Maryland, United States of America, available at: , accessed on 15 May 2022.…”
Section: Methodsmentioning
confidence: 99%
“…The primers for quantification of C10orf55, C3orf35, C5orf38, CASC2, MEG3, MYCNOS, SFTA1P, SNHG3, and TMEM105 were described previously [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ] and are presented in Table 1 . The compatibility of all primers and their complementarity to the target sequence was checked using the Basic Local Alignment Search Tool (BLAST), National Center for Biotechnology Information (NCBI), Bethesda, Maryland, United States of America, available at: , accessed on 15 May 2022.…”
Section: Methodsmentioning
confidence: 99%
“…One group showed that CASC2 overexpression exhibited antitumor activities through sponging miR-24-3p in thyroid cancer ( 109 ). Another group reported that CASC2 increased radiotherapy sensitivity via sponging miR-155 in papillary thyroid cancer ( 112 ). Similarly, lncRNA CASC2 increased irradiation-triggered endoplasmic reticulum stress via regulation of PERK signaling pathway in NSCLC cells ( 113 ).…”
Section: Lncrnas Regulate the Expression Of F-box Proteinsmentioning
confidence: 99%
“…LncRNA CASC2, located at chromosome 10q26, was first identified to be dysregulated in endometrial carcinoma ( 27 ). CASC2, as a tumor suppressor, was subsequently discovered to play a crucial part in multiple tumor diseases, including pancreatic cancer ( 28 ), papillary thyroid cancer ( 29 ), cholangiocarcinoma ( 30 ), glioma ( 31 ), and so on. Given the critical role of the NF-κB pathway in HCC resistance to TRAIL, identifying more lncRNA CASC2/miRNA axes modulating the NF-κB pathway in HCC cells might provide novel targets for restoring TRAIL sensitivity.…”
Section: Introductionmentioning
confidence: 99%